Countermeasures for Two-Way Development of Police Sports and Police Skills in Police Colleges and Universities - Xu, Guangming (Journal of Theory and Practice of Social Science, 2024)
Police sports and police skills are the two basic contents of police college teaching, in the present stage of police college teaching, most of the teaching ignored the two-way development of police sports and police skills, this paper mainly in view of the current situation of police colleges and universities put forward countermeasures to promote the two-way development of police sports and police skills. With the continuous development of information technology, people's life has officially entered the information age. In the information age, people need to process many data in their work and life. Not only the amount of data, but also the timeliness and accuracy of data processing are required. Big data technology emerges with this demand. Nowadays, big data technology has been widely used in common fields, and the marketing environment has changed a lot. Based on this, this paper studies the transformation path of marketing in the era of data transformation.